The use of Socratic Method as a teaching/learning tool to develop students’ critical thinking: a review of literature - Zare, Pezhman; Mukundan, Jayakaran (M S Thirumalai, 2015)
This paper reviews the literature on Socratic Method as a teaching/learning tool to enhance critical thinking skills. It starts with a short history of Socratic Method by introducing its founder and briefly provides an overall picture of the method. Then, a number of definitions of critical thinking is presented and discussed. Next, taxonomy of Socratic questioning is presented. The taxonomy provides a detailed description of questions that can be used when employing Socratic Method. Afterwards, a number of previous studies are reviewed to show the influence of Socratic approach on critical thinking skills. Finally, a brief conclusion will close the paper.